Comparative Effects of Diet-Induced Lipid Lowering Versus Lipid Lowering Along With Apo A-I Milano Gene Therapy on Regression of Atherosclerosis. (May 2016) - Wang, Lai; Tian, Fang; Arias, Ana; Yang, Mingjie; Sharifi, Behrooz G.; Shah, Prediman K.
Apolipoprotein A-1 (Apo A-I) Milano, a naturally occurring Arg173 to Cys mutant of Apo A-1, has been shown to reduce atherosclerosis in animal models and in a small phase 2 human trial. We have shown the superior atheroprotective effects of Apo A-I Milano (Apo A-IM) gene compared to wild-type Apo A-I gene using transplantation of retrovirally transduced bone marrow in Apo A-I/Apo E null mice. In this study, we compared the effect of dietary lipid lowering versus lipid lowering plus Apo A-IM gene transfer using recombinant adeno-associated virus (rAAV) 8 as vectors on atherosclerosis regression in Apo A-I/Apo E null mice. All mice were fed a high-cholesterol diet from age of 6 weeks until week 20, and at 20 weeks, 10 mice were euthanized to determine the extent of atherosclerosis. After 20 weeks, an additional 20 mice were placed on either a low-cholesterol diet plus empty rAAV (n = 10) to serve as controls or low-cholesterol diet plus 1 single intravenous injection of 1.2 × 10 12 vector genomes of adeno-associated virus (AAV) 8 vectors expressing Apo A-IM (n = 10). At the 40 week time point, intravenous AAV8 Apo A-IM recipients showed a significant regression of atherosclerosis in the whole aorta ( P < .01), aortic sinuses ( P < .05), and brachiocephalic arteries ( P < .05) compared to 20-week-old mice, whereas low-cholesterol diet plus empty vector control group showed no significant regression in lesion size. Immunostaining showed that compared to the 20-week-old mice, there was a significantly reduced macrophage content in the brachiocephalic ( P < .05) and aortic sinus plaques ( P < .05) of AAV8 Apo A-IM recipients. These data show that although dietary-mediated cholesterol lowering halts progression of atherosclerosis, it does not induce regression, whereas combination of low-cholesterol diet and AAV8 mediated Apo A-I Milano gene therapy induces rapid and significant regression of atherosclerosis in mice. These data provide support for the potential feasibility of this approach for atherosclerosis regression.